The Role and Effectiveness of Mobile Applications and Online Platforms in Enhancing Tourism Services - Doniyorbek Tursunov; Muhamadali Ismailov (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis provides a scientific and practical analysis of the role of mobile applications and online platforms in the modern tourism industry, as well as their impact on consumer behavior and the quality indicators of tourism services. It examines the integration of global platforms such as Booking, Airbnb, and TripAdvisor, along with local mobile applications, in travel planning, accommodation booking, navigation, and interactive service delivery, and offers strategic proposals for their development within the tourism market of Uzbekistan.